PROPERTI PSIKOMETRI BAHASA INDONESIA DARI KUALITAS HIDUP TERKAIT KESEHATAN TERHADAP REMAJA (KINDL-R) - Zefanya, Ersa; Purba, Fredrick D. (Jurnal Psikologi, 2024)
Adolescence and smoking present a significant public health concern, with estimates suggesting 30% of global smokers fall within this age group. Smoking negatively impacts adolescents' daily lives across physical, psychological, and social domains, collectively known as Health-Related Quality of Life (HRQoL). This study aimed to evaluate the psychometric properties of the KINDL-R HRQoL instrument for Indonesian children and adolescents. The study involved 206 adolescents aged 14-17 years in Bandung, recruited using purposive sampling. Results of the development of the Indonesian version of the KINDL-R adaptation using Confirmatory factor analysis (validity) supported a six-dimensional model (p < .05). Internal consistency reliability (reliability) was good, with Cronbach's alpha values = 0.92. Test-retest reliability was also satisfactory, with item discrimination values exceeding 0.40 for most items. These findings suggest that the KINDL-R demonstrates good reliability and validity for assessing HRQoL in Indonesian adolescents.